Machine Learning for Multimodal Interaction - Popescu-Belis, Andrei (H: Springer, 2017)
This book constitutes the refereed proceedings of the 5th International Workshop on Machine Learning for Multimodal Interaction, MLMI 2008, held in Utrecht, The Netherlands, in September 2008.